Functional Metagenomics of the Bronchial Microbiome in COPD - Millares, Laura (PLoS One, 2015)
The course of chronic obstructive pulmonary disease (COPD) is frequently aggravated by exacerbations, and changes in the composition and activity of the microbiome may be implicated in their appearance. The aim of this study was to analyse the composition and the gene content of the microbial community in bronchial secretions of COPD patients in both stability and exacerbation. Taxonomic data were obtained by 16S rRNA gene amplification and pyrosequencing, and metabolic information through shotgun metagenomics, using the Metagenomics RAST server (MG-RAST), and the PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) programme, which predict metagenomes from 16S data. Eight severe COPD patients provided good quality sputum samples, and no significant differences in the relative abundance of any phyla and genera were found between stability and exacerbation. Bacterial biodiversity (Chao1 and Shannon indexes) did not show statistical differences and beta-diversity analysis (Bray-Curtis dissimilarity index) showed a similar microbial composition in the two clinical situations. Four functional categories showed statistically significant differences with MG-RAST at KEGG level 2: in exacerbation, Cell growth and Death and Transport and Catabolism decreased in abundance [1.6 (0.2–2.3) vs 3.6 (3.3–6.9), p = 0.012; and 1.8 (0–3.3) vs 3.6 (1.8–5.1), p = 0.025 respectively], while Cancer and Carbohydrate Metabolism increased [0.8 (0–1.5) vs 0 (0–0.5), p = 0.043; and 7 (6.4–9) vs 5.9 (6.3–6.1), p = 0.012 respectively]. In conclusion, the bronchial microbiome as a whole is not significantly modified when exacerbation symptoms appear in severe COPD patients, but its functional metabolic capabilities show significant changes in several pathways.